2016
DOI: 10.1126/sciadv.1600889
|View full text |Cite
|
Sign up to set email alerts
|

Implantable microcoils for intracortical magnetic stimulation

Abstract: Magnetic stimulation from cortically implantable microcoils can activate neuronal circuits with high selectivity and reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(194 citation statements)
references
References 60 publications
6
186
0
Order By: Relevance
“…The size of the coils, number of turns, their magnetic core, and locations with respect to the brain are optimized in a way that fulfil multiple objectives: a) the size of the coils and their locations with respect to the brain should be optimized such that the produced magnetic fields by two coils can interfere at any area and any depth inside the brain with a high spatial resolution. Unlike TMS technique, which can only stimulate the peripheral regions and lacks a high spatial resolution, MTI technique can focus the magnetic or electric fields at deep brain area; b) the generated electric field gradient, which is the most important parameter for magnetic brain stimulation, should be higher than the threshold value required for brain stimulation, which is about 11k V/m 2 [12,13]; c) the designed coils should be able to efficiently operate at frequencies up to 50kHz. This is because the induced electric field of the coils increases linearly by increasing the operational frequency, meaning that we can generate very large electric fields and go above required threshold value by increasing the frequency and without increasing the current, heavily reducing the generated heat and power consumption.…”
Section: -Design Simulation and Concept Validation Of Magnetic Temmentioning
confidence: 99%
“…The size of the coils, number of turns, their magnetic core, and locations with respect to the brain are optimized in a way that fulfil multiple objectives: a) the size of the coils and their locations with respect to the brain should be optimized such that the produced magnetic fields by two coils can interfere at any area and any depth inside the brain with a high spatial resolution. Unlike TMS technique, which can only stimulate the peripheral regions and lacks a high spatial resolution, MTI technique can focus the magnetic or electric fields at deep brain area; b) the generated electric field gradient, which is the most important parameter for magnetic brain stimulation, should be higher than the threshold value required for brain stimulation, which is about 11k V/m 2 [12,13]; c) the designed coils should be able to efficiently operate at frequencies up to 50kHz. This is because the induced electric field of the coils increases linearly by increasing the operational frequency, meaning that we can generate very large electric fields and go above required threshold value by increasing the frequency and without increasing the current, heavily reducing the generated heat and power consumption.…”
Section: -Design Simulation and Concept Validation Of Magnetic Temmentioning
confidence: 99%
“…Additionally, other researchers are starting to use magnetic stimulation from implantable micro-coils as an alternative to conventional micro-electrodes. Coils are attractive because they overcome many of the limitations of conventional electrodes since magnetic stimulation does not require the injection of electrical currents and asymmetric fields from coils can be used to improve focal activation of specific subsets of neurons (Lee et al, 2016).…”
Section: Electrode-to-tissue Interface Issuesmentioning
confidence: 99%
“…Although subretinal 344 prostheses such as Alpha-IMS (Stingl et al, 2015) have electrodes in close proximity to bipolar 345 cells, in vitro animal studies have found that subretinal stimulation with 1 ms pulses also directly 346 activates retinal ganglion cells at thresholds statistically similar to those of inner retinal cells 347 (Boinagrov et al, 2014;Eickenscheidt et al, 2012;Tsai et al, 2009). Similarly, axonal stimulation 348 is expected to be an issue for cortical implants, since passing axons from neurons located in distant 349 parts of the brain have been shown to be highly sensitive to electrical stimulation (Histed et al,350 2009; Lee et al, 2016;Ranck, 1975). 351…”
Section: Phosphene Shape Is Mediated By Axonal Stimulation 331mentioning
confidence: 99%